PENGARUH REWARD ATTRACTIVENESS, KNOWLEDGE BENEFIT, REQUIRED EFFORT, GROUP BELONGINGNESS DAN DISCLOSURE COMFORT TERHADAP EXPERIENTIAL BENEFIT CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY - Krisnawati, Wenti (Jurnal Manajerial, 2019)
Purpose from this study was to determine the effect of attractiveness reward on experiential benefit, knowledge benefit on experiential benefit, required effort on experiential benefits, group belongingness to customer satisfaction, disclosure closure to customer satisfaction, group belongingness to customer loyalty, disclosure comfort to customer loyalty, experiential benefits to customer satisfaction and customer satisfaction to customer loyalty. The population used in this study is all Excelso customers who have amember card coffee shop Excelso. The number of samples in this study were 178 respondents. The analysis technique used is Structural Equation Modeling (SEM) using the AMOS 16.0 program. The results showed a significant influence between variable reward attractiveness on experiential benefit, knowledge benefit on experiential benefit, required effort on experiential benefits, group belongingness to customer satisfaction, disclosure closure on customer satisfaction, experiential benefits for customer satisfaction, and customer satisfaction for customer loyalty. Whereas variables that have no effect between variables group belongingness to customer loyalty and disclosure comfort to customer loyalty due to loyalty are influenced by satisfaction. Customers will be loyal when they are satisfied with the products or services offered by the company.